2018
DOI: 10.1007/s00701-018-3525-9
|View full text |Cite
|
Sign up to set email alerts
|

Visual field deficits after epilepsy surgery: a new quantitative scoring method

Abstract: BackgroundAnterior temporal lobectomy (ATL) as a treatment for drug-resistant temporal lobe epilepsy (TLE) frequently causes visual field deficits (VFDs). Reported VFD encompasses homonymous contralateral upper quadrantanopia. Its reported incidence ranges from 15 to 90%. To date, a quantitative method to evaluate postoperative VFD in static perimetry is not available. A method to quantify postoperative VFD, which allows for comparison between groups of patients, was developed.MethodsFifty-five patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The distinct dispersion characteristics of ultrahigh field 7-T DWI allowed for the characterization of optic tract injuries in patients experiencing cross-compression prior to surgery, offering valuable insights into the prognosis of vision recovery. In another study, van Lanen et al ( 68 ) developed a quantitative scoring method to evaluate VFDs following anterior temporal lobectomy using static visual field tests. They evaluated the feasibility of this approach for clinical applications.…”
Section: Resultsmentioning
confidence: 99%
“…The distinct dispersion characteristics of ultrahigh field 7-T DWI allowed for the characterization of optic tract injuries in patients experiencing cross-compression prior to surgery, offering valuable insights into the prognosis of vision recovery. In another study, van Lanen et al ( 68 ) developed a quantitative scoring method to evaluate VFDs following anterior temporal lobectomy using static visual field tests. They evaluated the feasibility of this approach for clinical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, visual deficits should be considered when performing TLE surgery. A recent study proposed a novel quantitative scoring method to assess postoperative visual field deficits after TLE surgery 30 . This method shows potential as a valuable addition to the routine presurgical evaluations before TLE surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complications in this study were loss of the menace response and atrophy of the temporal muscles. Visual abnormalities and temporal muscle damage are also common adverse effects in humans [ 31 , 35 , 41 ]. However, their occurrence is thought to be an inevitable secondary iatrogenic effect when the benefits of surgery, i.e., liberation from severe seizures, are considered.…”
Section: Discussionmentioning
confidence: 99%
“…MRI and pathology confirmed that the sites of visual pathway damage in this study were mainly the optic tract and internal capsule. In human ATL, visual field defects are frequently reported as a postoperative complication, of which contralateral superior quadrantanopia is the most common symptom [ 4 , 41 ]. This deficit is caused by damage to the anterior portion of the optic radiation and anterior bending of the temporal radiation in the temporal lobe (Meyer’s loop).…”
Section: Discussionmentioning
confidence: 99%